Performance comparison prediction of energy states of atoms in doxorubin and docetaxel using various computational simulations for cancer treatment - Nair B.J, Bipin; K.V, Vishnu (International Journal of Engineering and Technology, 2018)
Every atoms or compounds must have ground state as well as excited state when they are participating in chemical reactions. Drug is also a chemical compound which also has the two states. Computing the physical properties of a drug compound and calculate its energy states and Comparing the ground state and excited state performance of aromatic cyclic cancer drugs like doxorubicin and docetaxel using various types of cheminformatics methods.in our work we are using so many physical properties like surface area of an atom etc. to check the efficiency of drug.